Production of Zinc Borate for Pilot-Scale Equipment and Effects of Reaction Conditions on Yield - Bardakci, Melek; Baran Acarali, Nil; Tugrul, Nurcan; Moroydor Derun, Emek; Piskin, Mehmet Burcin (KAUNAS UNIV TECH, 2013)
In this study, zinc borate (ZB) was synthesized by reacting zinc oxide and boric acid in the presence of standard ZB (w/w, in terms of boric acid) in order to promote crystallization. The effects of seed, H3BO3/ZnO (boric acid/zinc oxide) ratio, reaction time, water volume, reaction temperature and cooling temperature on yield were investigated for pilot-scale equipment. The results indicated that the addition of seed (w/w) to a saturated solution of reactants increased the yield of the reaction. The results of reaction yields obtained from either magnetically or mechanically stirred systems were compared. At various reaction times, the optimal yield was 86.78 % in a saturated aqueous solution. The products were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and Thermogravimetric /Differential Thermal Analysis (TG/DTA). The results displayed that ZB was successfully produced under the optimized reaction conditions and the product synthesized had high thermal stability.
Keywords: boric acid; seed; yield; zinc borate; zinc oxide; BORIC-ACID; 2ZNO-CENTER-DOT-3B(2)O(3)CENTER-DOT-3H(2)O; Materials Science